Mites of Greenhouses Identification, Biology and Control - Zhang, Zhi-Qiang; Ebooks Corporation (Wallingford : CABI, 2003)
Mites are major pests of greenhouse crops and cause significant economic impact. This book describes the biology, identification and control of such mites. Topics covered include: introduction to the Acari; keys to orders, families and selected species; and collecting, rearing and studying mites.
Contenido: Table of Contenido: Preface; Acknowledgements; Part I Introduction; 1 Greenhouses, Plants & Mites; 2 Introduction to Acari; 3 Methods & Techniques; Part II Pest Mites; 4 Spider Mites; 5 False Spider Mites; 6 Tarsonemid Mites; 7 Eriophyoid Mites; 8 Acarid Mites; 9 Other Pest Mites; Part III Beneficial Mites; 10 Phytoseiid Mites; 11 Laelapid Mites; 12 Other Beneficial Mites; Part IV Accessories; 13 Glossary; 14 Appendix; 15 Index
Libro electronico adquirido a perpetuidad con la editorial CABI
Keywords: ACAROS FITOFAGOS